Greater sage‐grouse apparent nest productivity and chick survival in Carbon County, Wyoming. Issue 2 (1st March 2016) - Schreiber, Leslie A.; Hansen, Christopher P.; Rumble, Mark A.; Millspaugh, Joshua J.; Thompson, Frank R.; Gamo, R. Scott; Kehmeier, Jon W.; Wojik, Nate
Abstract : Greater sage‐grouse Centrocercus urophasianus populations across North America have been declining due to degradation and fragmentation of sagebrush habitat. As part of a study quantifying greater sage‐grouse demographics prior to construction of a wind energy facility, we estimated apparent net nest productivity and survival rate of chicks associated with radio‐equipped female sage‐grouse in Carbon County, Wyoming, USA. We estimated apparent net nest productivity using a weighted mean of the average brood size and used a modified logistic‐exposure method to estimate daily chick survival over a 70‐day time period. Apparent nest productivity was 2.79 chicks per female (95% CI: 1.46–4.12) in 2011, 2.00 chicks per female (95% CI: 1.00–3.00) in 2012, and 1.54 chick per female (95% CI: 0.62–2.46) in 2013. Chick survival to 70 days post‐hatch was 19.10% (95% CI: 6.22–37.42%) in 2011, 4.20% (95% CI: 0.84–12.31%) in 2012, and 16.05% (95% CI: 7.67–27.22%) in 2013. These estimates were low, yet within the range of other published survival rates. Chick survival was primarily associated with year and chick age, with minor effects of average temperature between surveys and hatch date. The variability in chick survival rates across years of our study suggests annual weather patterns may have large impacts on chick survival. Thus, management actions that increase the availability of food and cover for chicks may be necessary, especially during years with drought and above‐average spring temperatures.